1976
DOI: 10.1063/1.322935
|View full text |Cite
|
Sign up to set email alerts
|

1/f noise measurements for characterizing multispot low-Ohmic contacts

Abstract: The patchiness of contacts can be determined from measurements of 1/f noise and contact resistance on a number of contacts of different diameters made by the same method. If a contact consists of k conducting spots with average radius a, k and a can be determined if the distance between the spot centers is at least 2.5 times the spot diameter. Using the developed multispot contact model, the results of the 1/f noise analysis are in good agreement with multispot parameters obtained from microscopic investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…For example, it has been shown that alloying of AuSi contact film on GaAs at temperatures 450°C and higher causes the formation of globules, thus creating a multispot contact area. 36 It is possible that a similar effect could occur in a Pt/ GaN contact system. In the S50 device we assume that a local current density of at least 2 ϫ 10 6 A/cm 2 must exist at the rim of the semitransparent window and the area around the bonded wire.…”
Section: Agingmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, it has been shown that alloying of AuSi contact film on GaAs at temperatures 450°C and higher causes the formation of globules, thus creating a multispot contact area. 36 It is possible that a similar effect could occur in a Pt/ GaN contact system. In the S50 device we assume that a local current density of at least 2 ϫ 10 6 A/cm 2 must exist at the rim of the semitransparent window and the area around the bonded wire.…”
Section: Agingmentioning
confidence: 97%
“…A very noisy contribution is assumed to be in series with an almost noise-free contribution similar to multispot contact problems. 9,[34][35][36] The onset of contact degradation leads to current crowding and enhanced noise. The noise of a large part of the series resistance can remain unaffected by the degradation.…”
Section: Agingmentioning
confidence: 99%
“…The patchiness parameters and are the number of spots and the spot radius, respectively, while is the distance between the spot centers. The resistance and noise were calculated for a general multispot contact [7]. The electrical contact area is smaller than the apparent conducting area , which explains the discrepancy between experimentally observed resistance and calculated resistance from .…”
Section: Model For the Noise In Conductive Adhesive Bondsmentioning
confidence: 95%
“…The analysis of the results is based on a model for multispot contacts in [7]. In a special case of multispot contacts with -conducting spots, with diameter , far apart from each other, and can be calculated [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Patchy contacts at a metal-semiconductor interface have been studied quantitatively by using contact resistance and noise measurements. 6 1/f noise measurements were recommended as a diagnostic tool for research on thick-films, 1,7 for thinfilm metalization patterns 8 and for quantitative characterization of contacts in general. 6'9 Considering the distribution of metal oxide grains in the poor conducting matrix, most thick-film resistors are homogeneous.…”
Section: -Smentioning
confidence: 99%